Cutaneous Histologic Artifact Associated with the Use of a Needle‐Free Anesthesia Device for Skin Biopsy. Issue 5 (14th February 2013) - Smith, Jessica A.; Zhang, Cathryn Z.; Rupani, Reena; Lian, Fangru
Abstract A needle‐free system that delivers lidocaine to the dermis using pressurized gas is often used as an alternative anesthetic for venipuncture and intravenous catheterization in children. This case report illustrates the potential histologic artifacts that may arise when using a needleless device for a cutaneous punch biopsy. We suggest against using a needleless system for pediatric skin biopsies.